Programmed Death Ligand 1 Testing of Endobronchial Ultrasound–guided Transbronchial Needle Aspiration Samples Acquired For the Diagnosis and Staging of Non–Small Cell Lung Cancer. Issue 1 (January 2020) - Smith, Allister; Wang, Hangjun; Zerbo, Alix; Beaudoin, Stéphane; Ofiara, Linda; Fiset, Pierre-Olivier; Benedetti, Andrea; Gonzalez, Anne V.
Abstract : Rationale: Immunotherapy has become an integral part of management in patients with advanced non–small cell lung cancer (NSCLC). Programmed death ligand 1 (PD-L1) expression in at least 50% of tumor cells on histologic samples has been correlated with improved efficacy of the immune checkpoint inhibitor pembrolizumab. A limited number of studies have examined the suitability of endobronchial ultrasound–guided transbronchial needle aspiration (EBUS-TBNA) specimens for assessment of PD-L1 status. Objective: We sought to examine the feasibility and results of PD-L1 testing performed on EBUS-TBNA samples acquired for the diagnosis and staging of NSCLC. Materials and Methods: Patients were identified from a prospectively maintained pathology database. Baseline characteristics were tabulated. Hematoxylin and eosin slides were reviewed to categorize cellularity between <100, 100 to 500, and >500 viable tumor cells. Samples were tested using Dako's PD-L1 IHC 22C3 pharmDx kit, with a minimum of 100 viable tumor cells. For patients in whom additional tissue samples were available, the results of PD-L1 testing were compared. Results: PD-L1 testing was attempted on 120 EBUS-TBNA samples. The most common NSCLC subtype was adenocarcinoma (78%). Seventy-six specimens (63%) had a cellularity >500 tumor cells. Among 110 of 120 (92%) patients with an adequate endobronchial ultrasound (EBUS) sample, 53 of 110 (48.2%) had high PD-L1 expression, defined as a Tumor Proportion Score ≥50%. EBUS PD-L1 results were concordant with an available histologic sample in 14 of 18 patients (78%), with no false-negative results. Conclusion: PD-L1 testing was feasible in the majority of EBUS-TBNA samples acquired for the diagnosis and staging of NSCLC. Comparison of EBUS results with histologic samples revealed moderate concordance, with no false-negative results. Abstract : Supplemental Digital Content is available in the text.